The Role of Digital Capabilities and Financial Literacy in Shaping Crypto Investment: A Systematic Review Digital Financial Era - Eka Hadiwijaya; Siti Hernita Oktavia; Taufik Andriadi; Siti Mujanah (Business Management, 2025)
This article aims to examine the role of digital capabilities and financial literacy in shaping crypto investment behavior through a systematic literature review approach. The method used is systematic literature review based on the PRISMA protocol, by analyzing 15 articles published in 2018–2024 from various national and international databases. The results of the study show that the combination of digital capabilities and financial literacy significantly shapes rational, adaptive, and risk-resistant investment behavior in the crypto ecosystem. This study produces a conceptual model that places these two variables as the foundation for human resource (HR) transformation in facing the era of decentralized finance (Decentralized Finance). Policy implications offered include cross-disciplinary curriculum design and community-based training to enhance community preparedness. Novelty of this article lies in the simultaneous integration of digital capabilities and financial literacy in the context of crypto investment and digital HR transformation, which has not been widely discussed in previous studies.